2014
DOI: 10.1021/am5028296
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Synthesis of CaIn2S4-Reduced Graphene Oxide Nanocomposites with Increased Photocatalytic Performance

Abstract: A series of CaIn2S4-reduced graphene oxide (RGO) nanocomposites with different RGO contents were fabricated using a facile hydrothermal approach. During the hydrothermal process, the reduction of graphene oxide to RGO, in situ deposition of synthesized CaIn2S4 nanoparticles on RGO nanosheets and formation of chemical-bonding CaIn2S4-RGO nanocomposites were performed simultaneously. Under visible light irradiation, the as-prepared CaIn2S4-RGO nanocomposites showed enhanced photocatalytic performance for rhodami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 47 publications
3
39
0
Order By: Relevance
“…It could be clearly observed that the position of the VB edge of CaIn 2 S 4 and g-C 3 N 4 are located at 1.03 and 1.71 eV, respectively, which are consistent with the previous reports. 26,38 Combined with the calculated band gaps, the conduction band (CB) edge of CaIn 2 S 4 and g-C 3 N 4 are estimated at −0.98 eV and −1.12 eV, respectively. Figure 5a shows the photocatalytic H 2 production activity of g-C 3 N 4 , CaIn 2 S 4 , and CaIn 2 S 4 /g-C 3 N 4 heterojunction nanocomposites with different contents of CaIn 2 S 4 from an aqueous solution containing 0.5 M Na 2 S and 0.5 M Na 2 SO 3 under UV light irradiation (triggered by 12 W UV-LEDs light).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be clearly observed that the position of the VB edge of CaIn 2 S 4 and g-C 3 N 4 are located at 1.03 and 1.71 eV, respectively, which are consistent with the previous reports. 26,38 Combined with the calculated band gaps, the conduction band (CB) edge of CaIn 2 S 4 and g-C 3 N 4 are estimated at −0.98 eV and −1.12 eV, respectively. Figure 5a shows the photocatalytic H 2 production activity of g-C 3 N 4 , CaIn 2 S 4 , and CaIn 2 S 4 /g-C 3 N 4 heterojunction nanocomposites with different contents of CaIn 2 S 4 from an aqueous solution containing 0.5 M Na 2 S and 0.5 M Na 2 SO 3 under UV light irradiation (triggered by 12 W UV-LEDs light).…”
Section: Resultsmentioning
confidence: 99%
“…26,27 The formed two-dimensional heterostructure of the nanocomposite photocatalyst could not only enhance the interfacial contact area between CaIn 2 S 4 and g-C 3 N 4 but also facilitate separation of charge carriers. As such, the CaIn 2 S 4 /g-C 3 N 4 heterojunction nanocomposites exhibited enhanced H 2 evolution and photocatalytic degradation of MO activities under visible-light irradiation in comparison to pristine g-C 3 N 4 and CaIn 2 S 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The XPS results for CIS are in accord with standard reference XPS spectra, and further validate the oxidation state assignments for Ca, In, and S in the CIS marigold flowers as +2, +3, and −2, respectively. 25,26,30 From Figure 5c and Figure S5a 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 composites, respectively. A peak related to the 3d 3/2 level of In 3d with a binding energy of 453.26 eV was 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21...…”
Section: Xps Analysismentioning
confidence: 99%
“…However, previous reports for CIS have described a mixture of nanoparticles and nanosheet-like morphologies. 25,26,30 Figure 2c shows the spherical morphology of TiO 2 , which was unchanged upon the addition of CIS (Figure 2d the 10%-CIS/TNP composite (Figure 2h), the added CIS appears to exhibit a curved sheet or tube-like structure. It is possible that, while stirring during preparation, some of the thin petals of the microspheres were exfoliated and formed curled sheets, which were subsequently rolled into tube-like structures.…”
Section: Pxrd Analysismentioning
confidence: 99%
“…Recent study found that ternary CaIn 2 S 4 , first synthesized using a facile hydrothermal method, can produce hydrogen from pure water without any cocatalysts under visible light irradiation [14]. For example, Ding synthesized the CaIn 2 S 4 Reduced Graphene Oxide Nanocomposites for efficient RhB degradation under visible light irradiation [17]. Among various strategies, the rapid separation-transfer-transformation of photo-generated charge carriers is a key issue which should be addressed [15].…”
Section: Introductionmentioning
confidence: 99%